Improving Bearing Capacity by Skirted Foundation: A Review Study - ., Ahmed S. Abdulrasool; ., Sura A. Abbas; ., Shaimaa M. Abdulrahman (Iraqi Journal of Civil Engineering, 2021)
The difficulty that faces the geotechnical engineers how to find the alternative and effective method to improve bearing capacity and reduce foundation settlement. Therefore, the skirt is considered one of the methods to improving the shallow foundation bearing capacity on different soil. The mechanism of skirt work is confinement soil below the foundation and decrease settlement of the foundation. Soil engineers are worked to devise this method as an alternative to pile foundation for conventional buildings. This paper reviews most of these studies of skirted foundations with different types of soil including laboratory tests, field tests, centrifuge models, numerical method and theoretical analysis; these studies are used in investigation the behaviors skirted foundations.